Museum as a tool, art history as speech (Palíndromo, 2020)
We intend to build reflections about the relationship between museum and art history, from the perspective of the discourses construction. For that we will bring discussions about the museum - as well as the archive and the library - from authors such as Michel Foucault and Jacques Derrida, who approach these institutions as being legitimate to affirm narratives. Then we will seek to sustain on the one hand the relationship between structure, environment and modernity; and on the other hand its transformation to poststructuralism, the dissolution of the specific medium for the art work and postmodernity.
Keywords: museum; art history; structure; discourse